STUDI EKSPERIMEN IMPLEMENTASI MODEL PEMBELAJARAN EXAMPLE NON-EXAMPLE PADA PEMBELAJARAN MENULIS TEKS PROSEDUR - Rini Andriani; Andarini Rani Prabowati; Hamdani (Journal of Education for The Language and Literature of Indonesia, 2023)
This experimental research was motivated by the problem of learning Indonesian, namely the low score of student learning outcomes in writing procedure texts. Based on this research, it aims to determine the effect of the Example Non-example learning model and to create students to be more active, creative, and productive. This study used a pre-experimental design with a one group pretest-posttest design (one group pretest-posttest). The data source for this research was 7th grade E students with a sample of 37 people. This research obtained quantitative and qualitative data. Quantitative data processing includes the normality test, Wilcoxon Signed Ranks Test, and statistical tests. Calculations and data testing are assisted by using Microsoft Excel 2013 and IBM SPSS Statistics 29 for Windows. Quantitative data processing is obtained from implementation sheets or activity sheets of teachers and students in classes that use the example non-example learning model. These results indicate that the average pretest score of students is 48.446 and the average posttest score is 83.514. To find out whether it has an effect or not, a normality test is carried out in class VII E, originating from a non-normally distributed population. The next step is to carry out a statistical test, the Wilcoxon signed ranks test. The results in the sig column (2 tailed) are <.001, because the probability is <0. 05 then H0 is rejected, meaning that there is a difference in the ability to write procedural texts using the example non-example learning model for class VII students during the pretest and posttest by using the text-based example non-example learning model.